Efficacy and Safety of the Cudrania tricuspidata Extract on Functional Dyspepsia: A Randomized Double-Blind Placebo-Controlled Multicenter Study - Jinyoung Shin (MDPI AG, 2021)
Cudrania tricuspidata is a folk remedy used to treat inflammation in patients with tumors or liver damage. This study investigated the efficacy of Cudrania tricuspidata extract (CTE) for relieving the symptoms of functional dyspepsia. In an 8-week, randomized, double-blind, placebo-controlled study, 100 adults with any condition featured in the Rome IV criteria and a Gastrointestinal Symptoms Scale (GIS) score ≥4 were randomly allocated to take either a placebo (maltodextrin) or a 50 mg CTE tablet, which equally included celluloses, magnesium stearate, and silicon dioxide, twice daily, 20 January 2020, and 3 August 2020. Among the 83 participants finally analyzed, the CTE group was associated with a significant reduction in the gastrointestinal symptom rating scale (day 0: 8.0 ± 5.2, day 28: 4.7 ± 3.9, and day 56: 2.3 ± 2.4, p < 0.001, respectively) in comparison with the control group (day 0: 8.1 ± 4.7, day 28: 7.8 ± 5.7, and day 56: 7.5 ± 6.6, p > 0.05) after adjusting for smoking, drinking, eating habits, stress levels, and caffeine intake. The CTE group resulted in significant improvements of GIS, Nepean Dyspepsia Index (Korean version), and functional dyspepsia-related quality of life over time. There were no different adverse events (p = 0.523). These findings suggest that CTE is safe and efficacious for alleviating gastrointestinal symptoms in patients with functional dyspepsia.